A life course perspective on BMI in rural America. (May 2021) - Clark, Shelley
Abstract: Rural Americans are substantially more likely to be obese than their urban counterparts. A life course perspective offers insights into how growing up in rural areas may affect weight in young adulthood. Using data from the Panel Survey of Income Dynamics, this study follows the residential trajectories of 3157 respondents since birth. Living in a rural area during the critical period of early childhood (before age two) is predictive of higher BMI, while residence in later childhood and adolescence is not. Improving the health and wellbeing of rural mothers and infants could potentially help address the roots of rural obesity. Highlights: Life course analyses can help explain the rural-urban adult obesity gap. Cumulative rural exposure during childhood is not a predictor of adult obesity. Rural residence before age two is associated with obesity among young adults. Early childhood remains a critical period controlling for demographic characteristics and SES in childhood. Focusing on rural mothers and infants could reduce the adult obesity gap.